Pyramidal structure, political intervention and firms' tax burden: Evidence from China's local SOEs - Zhang, Min; M, Lijun; Zhang, Bo; Yi, Zhihong (Journal of Corporate Finance, 2016)
Using a sample of Chinese firms, we examine the influence of state-pyramids on corporate tax burden. We find results that state-pyramidal layers are significantly and negatively associated with effective tax rates, indicating that pyramids formed by the state protect local state-owned enterprises (SOEs) from political intervention. The results hold after controlling for potential endogeneity. We further find evidences suggesting that taxation is one of the channels through which state-controlled pyramids increase firm value. Our study contributes to both corporate finance and corporate tax literatures by documenting the role of pyramidal organizational structures in reducing local SOEs' tax burden.